2020
DOI: 10.1093/mnras/staa1083
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and characterization of cosmic filaments in galaxy cluster outskirts: strategies and forecasts for observations from simulations

Abstract: Upcoming wide-field surveys are well suited to studying the growth of galaxy clusters by tracing galaxy and gas accretion along cosmic filaments. We use hydrodynamic simulations of volumes surrounding 324 clusters from The ThreeHundred project to develop a framework for identifying and characterizing these filamentary structures and associating galaxies with them. We define three-dimensional reference filament networks reaching 5R200 based on the underlying gas distribution and quantify their recovery using mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 103 publications
8
62
3
Order By: Relevance
“…To understand this anisotropic environmental effect on the shape, we probed the possible relations between the accretion of infalling matter at the present time and the halo anisotropy proxies (both ellipticity and connectivity). In addition to the overall picture that groups and clusters are preferentially aligned with their main connected filaments as supported by previous theoretical (Gouin et al 2017;Okabe et al 2020a;Kuchner et al 2020) and observational (Einasto et al 2020;Okabe et al 2020b;Gouin et al 2020) studies, Morinaga & Ishiyama (2020) have recently shown that ellipticity is correlated with the filamentary accretion.…”
Section: Effect Of Cosmic Filament Accretion On Shapessupporting
confidence: 59%
See 1 more Smart Citation
“…To understand this anisotropic environmental effect on the shape, we probed the possible relations between the accretion of infalling matter at the present time and the halo anisotropy proxies (both ellipticity and connectivity). In addition to the overall picture that groups and clusters are preferentially aligned with their main connected filaments as supported by previous theoretical (Gouin et al 2017;Okabe et al 2020a;Kuchner et al 2020) and observational (Einasto et al 2020;Okabe et al 2020b;Gouin et al 2020) studies, Morinaga & Ishiyama (2020) have recently shown that ellipticity is correlated with the filamentary accretion.…”
Section: Effect Of Cosmic Filament Accretion On Shapessupporting
confidence: 59%
“…Groups and clusters with χ DS ≥ 1 were considered as dynamically relaxed (see, e.g., Kuchner et al 2020).…”
Section: Dynamical State Of Groups and Clustersmentioning
confidence: 99%
“…While the example shown in Fig. 1 offers an obvious clue that the identified network indeed traces the underlying structure of the density field, we refer the reader to Kuchner et al (2020), in which detailed tests of the filament extraction method on gas and mock galaxies in the same simulations, as well as comparisons between detections in 2D and 3D are presented.…”
Section: Filament Extraction Based On Gas Particlesmentioning
confidence: 99%
“…The hydrodynamical clusters consist of dark matter and gas particles, and star particles of variable masses, typically with mstar ∼ 4 × 10 7 h −1 M , produced by the stochastic star-formation that is implemented by gadgetX (Tornatore et al 2007;Murante et al 2010;Rasia et al 2015). TheThreeHundred dataset is described in more extensive detail in Cui et al (2018), and has been used in previous studies to examine cluster density profiles (Mostoghiu et al 2019;Li et al 2020), environments (Wang et al 2018;Kuchner et al 2020), ram pressure (Arthur et al 2019), the hydrostatic equilibrium mass bias (Ansarifard et al 2020), backsplash galaxies (Haggar et al 2020), and the shapes and alignments of galaxies (Knebe et al 2020). Table 1.…”
Section: Introductionmentioning
confidence: 99%